Double transition metal doped RuO2 acidic OER electrocatalyst and preparation method and application thereof

Through the preparation of a double transition metal doped RuO2 acidic OER electrocatalyst, the problem of difficulty in obtaining both activity and stability in the acidic OER reaction is solved, and an efficient, economical and environmentally friendly hydrogen production effect of electrolytic water is achieved.

CN119265608APending Publication Date: 2025-01-07海卓健新能源材料(上海)有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411678190.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing transition metal-doped RuO2 catalysts are difficult to achieve both activity and stability in acidic OER reactions and need further improvement.

Method used

Using double transition metal doped RuO2 acidic OER electrocatalyst, the chemical expression is (M1)x(M2)yRuO2, where M1 is Zr or Ti, and M2 is Mo, Nb or Tc, it is synthesized by hydrothermal reaction and high-temperature annealing to regulate The lattice parameters and electron density of the catalyst form a more stable oxide structure and active sites, reducing the amount of Ru to reduce costs.

Benefits of technology

The significant OER activity and stability of the catalyst are achieved, the production cost is reduced, and the efficient, economical and environmentally friendly electrolytic hydrogen production solution is provided. The catalyst exhibits long-term stability and high reactivity in an acidic environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265608A_ABST
    Figure CN119265608A_ABST
Patent Text Reader

Abstract

The invention discloses a double transition metal doped RuO2 acidic OER electrocatalyst and a preparation method and application thereof, relates to an OER electrocatalyst and a preparation method and application thereof, and aims to solve the technical problems of high overpotential and poor stability of the existing transition metal doped RuO2 catalyst.The catalyst is (M1) x (M2) yRuO2, M1 is Zr or Ti, and M2 is a transition metal doped RuO2 catalyst or a transition metal doped RuO2 catalyst or a transition metal doped RuO2 catalyst or a transition metal doped RuO2 catalyst or a transition metal doped RuO2 catalyst or a transition metal doped RuO2 catalyst or a transition metal doped RuO2 catalyst or a transition metal doped RuO2 catalyst. M2 is Mo, Nb or Tc; x is equal to 0.02 to 0.1, and y is equal to 0.02 to 0.1. The preparation method comprises the following steps: adding ruthenium salt, M1 salt, M2 salt and ethanol into water, putting the obtained mixed solution into a homogeneous reactor for hydrothermal reaction, washing and drying the product, and annealing. According to the present invention, the prepared electrode is loaded on carbon paper to prepare the electrode for acidic OER electro-catalysis, has the overpotential of 224 mV under the current density of 10 mAcm <-2 >, has excellent stability within 200 h, and can be used in the field of water electrolysis hydrogen production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a RuO2 acidic OER electrocatalyst, belonging to the technical field of hydrogen production by electrolysis of water. Background Art

[0002] Hydrogen energy, as one of the renewable energy sources, can be produced by water electrolysis, which consists of two half reactions: the hydrogen evolution reaction (HER) occurring on the cathode side and the oxygen evolution reaction (OER) occurring on the anode side. However, the slow reaction kinetics of the four-electron oxygen evolution reaction (OER) on the anode side seriously hinders the efficiency of acidic water decomposition. Therefore, the water decomposition reaction is essentially controlled by the OER reaction. Generally, precious metal catalysts can effectively reduce the activation energy of the oxygen evolution reaction (OER), thereby achieving rapid water oxidation reaction at a lower potential.

[0003] So far, ruthenium-based and iridium-based materials remain the most advanced OER catalysts with satisfactory activity under acidic conditions. Compared with iridium, ruthenium has higher activity and its cost is less than one-tenth of that of iridium. Theoretically, RuO2 is closest to the top of a volcano among all kinds of oxides. Compared with other transition metal oxides, RuO2 has the highest activity and higher electrochemical stability in an acidic water electrolysis environment. At the same time, the surface properties and structure of RuO2 are easy to control, and it can be doped with appropriate elements to further improve its electrochemical performance and catalytic activity. However, it is difficult to achieve both activity and stability of existing transition metal-doped RuO2 catalysts, and further improvements to the catalyst are needed. Summary of the invention

[0004] The present invention aims to solve the technical problem that it is difficult to achieve both activity and stability of the existing transition metal-doped RuO2 catalyst, and to provide a double transition metal-doped RuO2 acidic OER electrocatalyst and its preparation method and application.

[0005] The chemical expression of a double transition metal doped RuO2 acidic OER electrocatalyst of the present invention is (M1) x (M2) yRuO2, wherein M1 is Zr or Ti; M2 is Mo, Nb or Tc; x=0.02-0.1, y=0.02-0.1. In the electrocatalyst of the present invention, the transition metal M1 (M1=Zr, Ti) helps to adjust the lattice parameters of RuO2 and the covalency of Ru-O, forming a more stable oxide structure, so that the material has more stable electrochemical properties. The transition metal M2 (M2=Mo, Nb, Tc) can regulate the electron density of Ru at the active site, form oxygen vacancies during the reaction, and update the active sites on the catalyst surface. At the same time, by doping the transition non-precious metal elements M1 and M2, the amount of Ru used can be reduced, thereby reducing the overall cost of the catalyst.

[0006] A double transition metal doped RuO2 acidic OER electrocatalyst of the present invention is synthesized by a two-step reaction of hydrothermal reaction and high temperature annealing. The specific preparation method is carried out according to the following steps:

[0007] 1. Weigh RuCl3·xH2O, transition metal M1 salt, transition metal M2 salt and ethanol, dissolve in water, and stir magnetically for 0.5 to 3 hours to obtain a mixed solution;

[0008] 2. Transfer the mixed solution to a polytetrafluoroethylene liner, cover it with a stainless steel outer liner, transfer it to a homogeneous reactor, heat it to 60-180°C and maintain it for 2-10 hours for high temperature reaction, cool it to room temperature after the reaction is completed, wash the product with pure water and ethanol alternately, collect it by centrifugation, and dry it in vacuum to obtain a precursor powder;

[0009] 3. Place the precursor powder in a high-temperature furnace, heat it to 200-800°C and maintain it for 0.5-6 hours for annealing, and then cool it to room temperature to obtain a double transition metal-doped RuO2 acidic OER electrocatalyst.

[0010] Furthermore, the mass fraction of Ru in the RuCl3·xH2O described in step 1 is 37%.

[0011] Furthermore, the amount of the transition metal M1 salt in step 1 satisfies the atomic ratio M1:Ru=(0.02-0.1):1; the amount of the transition metal M2 salt satisfies the atomic ratio M2:Ru=(0.02-0.1):1;

[0012] Furthermore, the mass percentage concentration of RuCl3·xH2O in the mixed solution described in step 1 is 95% to 98%.

[0013] Furthermore, the volume percentage concentration of anhydrous ethanol in the mixed solution described in step 1 is 20% to 60%.

[0014] The application of the above-mentioned double transition metal doped RuO2 acidic OER electrocatalyst is to prepare the double transition metal doped RuO2 acidic OER electrocatalyst into an electrode for use in the electrolysis of water to produce hydrogen.

[0015] Furthermore, the method for preparing an electrode using a double transition metal doped RuO2 acidic OER electrocatalyst is carried out in the following steps:

[0016] 1. Pretreatment of the carbon paper substrate: first, the carbon paper is cut into a rectangle of 1*1.5 cm; then, hydrochloric acid, ultrapure water and anhydrous ethanol are used in an ultrasonic cleaning machine to remove the oxide on the surface of the carbon paper by ultrasonic cleaning, and then vacuum drying is performed to obtain a carbon paper substrate;

[0017] 2. Add the double transition metal doped RuO2 acidic OER electrocatalyst to the dispersion, and then put it into an ultrasonic machine for ultrasonic treatment for 0.5 to 3 hours to form a uniform suspension;

[0018] 3. Evenly drop the suspension onto the carbon paper substrate and allow it to dry naturally to obtain the electrode.

[0019] Furthermore, the thickness of the carbon paper in step 1 is 210 μm, and the concentration of hydrochloric acid is 1 to 5 mol L -1 The purity of the anhydrous ethanol is 99.7%, the ultrasonic treatment time is 10 to 60 minutes, the drying temperature is 50 to 80° C., and the drying time is 1 to 10 hours.

[0020] Furthermore, the dispersion in step 2 is a mixture of anhydrous ethanol, Nafion solution, and PVDF; the mass fraction of the Nafion solution is 1 to 10 wt %; the volume ratio of anhydrous ethanol to the Nafion solution is 970:30; and each milliliter of the dispersion contains 0.1 to 0.9 mg of PVDF;

[0021] Furthermore, the loading amount of the double transition metal doped RuO2 acidic OER electrocatalyst on the carbon paper substrate described in step 3 is 0.5-2 mg cm -2 .

[0022] The beneficial effects of the present invention relative to the prior art are:

[0023] (1) The double transition metal doped RuO2 acidic OER electrocatalyst of the present invention, since the surface properties and structure of RuO2 are easy to control, the electronic structure and surface properties of the catalyst are controlled by introducing two different transition metal elements, and the double metal doping brings about a synergistic effect. The transition metal M1 (M1 = Zr, Ti) itself has good acid and alkali resistance. The introduction of M1 can inhibit the lattice oxygen from participating in the OER reaction, thereby preventing Ru from being excessively oxidized to soluble RuO4 during the OER process, thereby improving stability. The transition metal M2 (M2 = Mo, Nb, Tc) itself has a variety of oxidation states, and can form oxygen vacancies to update the active sites on the catalyst surface in the acidic OER reaction. At the same time, the electron density of the Ru active site can be controlled, thereby enhancing the intrinsic activity of the catalyst. The catalyst of the present invention exhibits significant OER activity and stability, and the prepared catalyst material has high purity.

[0024] (2) The preparation method of the double transition metal doped RuO2 acidic OER electrocatalyst of the present invention selects metal ruthenium salt, transition metal M1 salt and transition metal M2 salt as raw materials, accurately controls the size, morphology and surface diversity of the catalyst particles, ensures the uniform distribution of the double transition metal elements in the RuO2 catalyst, optimizes the crystallinity of the catalyst, improves its thermal stability and durability, and can achieve a specific composition of (M1) x (M2) y The RuO2 material can be prepared in a controlled manner, and the high-temperature annealing process can change the crystal structure of the metal oxide and introduce crystal defects to regulate the electronic distribution of the catalyst and improve the reaction activity of the catalyst. The method is simple in process, controllable in synthesis process, low in production cost, and has good applicability for industrial production.

[0025] (3) The catalyst prepared by the present invention reduces the amount of precious metal ruthenium by doping non-precious metals, thereby reducing the production cost of the catalyst, while maintaining or even improving the overall electrocatalytic performance, providing an efficient, economical and environmentally friendly solution.

[0026] In summary, the present invention provides a method for preparing a double transition metal doped RuO2 electrocatalyst by hydrothermal and annealing, which has low operation technical requirements and can be prepared on a large scale; the prepared catalyst exhibits high activity and long stability in acidic OER, and Zr 0.05 Mo 0.05 RuO2 at 10 mA cm -2 , 20mA cm -2 , 50mA cm -2 , 100mA cm -2 The current density of Zr 0.05 Mo 0.05The Tafel slope of the RuO2 catalyst is 91.2 mV dec -1 , lower than RuO2 (130.3mV dec -1 ) and commercial RuO2 (137.0mV dec -1 ), and showed excellent stability within 200 hours, and can be used in the field of hydrogen production by water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a preparation flow chart of the present invention;

[0028] Figure 2 is the Zr prepared in Example 1 0.05 Mo 0.05 Scanning electron microscope image of RuO2

[0029] Figure 3 is a scanning electron microscope image of RuO2 prepared in Comparative Example 1;

[0030] Figure 4 is the Zr prepared in Example 1 0.05 Mo 0.05 TEM image of RuO2;

[0031] Figure 5 is the Zr prepared in Example 1 0.05 Mo 0.05 Selected area diffraction pattern of RuO2;

[0032] Figure 6 is the Zr prepared in Example 1 0.05 Mo 0.05 XRD spectra of RuO2 and RuO2 prepared in Comparative Example 1 and standard XRD pattern of RuO2;

[0033] Figure 7 is the Zr prepared in Example 1 0.05 Mo 0.05 XPS images of RuO2 and RuO2 prepared in Comparative Example 1;

[0034] Figure 8 is the Zr prepared in Example 1 0.05 Mo 0.05 LSV performance diagram and Tafel slope diagram of acidic OER of RuO2, RuO2 prepared in Comparative Example 1 and commercial RuO2;

[0035] Fig. 9 is the Zr prepared in Example 1 0.05 Mo 0.05 EIS impedance diagrams and double layer capacitance values ​​C of acidic OER of RuO2, RuO2 prepared in comparative example 1 and commercial RuO2 dlFitting graph;

[0036] Fig.10 is the Zr prepared in Example 1 0.05 Mo 0.05 RuO2 and commercial RuO2 at 10 mA cm -2 Stability test diagram under current density;

[0037] Fig.11 is the Zr prepared in Example 1 0.05 Mo 0.05 RuO2 at 10 mA cm -2 XRD comparison before and after stability test under current density. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0039] Example 1: Double transition metal doped RuO2 acidic OER electrocatalyst Zr 0.05 Mo 0.05 The preparation method of RuO2 is carried out according to the following steps:

[0040] 1. Weigh 400 mg of RuCl3·xH2O, 17.1 mg of ZrCl4, 90.5 mg of (NH4)2MoO4 and 10 mL of ethanol and dissolve them in 10 mL of ultrapure water. Stir magnetically for 0.5 h to obtain a mixed solution. The mass fraction of Ru in RuCl3·xH2O is 37%.

[0041] 2. Transfer the mixed liquid to the polytetrafluoroethylene liner, put on the stainless steel outer liner, transfer it to the homogeneous reactor, and adjust the speed of the homogeneous reactor to 8r min -1 The temperature was raised to 120 °C, and the reaction time was controlled to be 10 h for high temperature reaction. After the reaction was completed, it was naturally cooled to room temperature. The product was washed three times with pure water and ethanol alternately, and then the speed was 10000 r min -1 The solid phase was collected by centrifugation at a centrifugal speed of , and vacuum dried in a vacuum drying oven at a temperature of 60°C for 6 hours to obtain a precursor powder;

[0042] 3. Place the precursor powder in a muffle furnace with air atmosphere at 5°C min -1 The temperature was raised to 400 °C at a heating rate and maintained for 2 h for annealing, and then cooled to room temperature to obtain the double transition metal doped RuO2 acidic OER electrocatalyst Zr 0.05 Mo 0.05 RuO2.

[0043] Comparative Example 1: This comparative example is to prepare the acidic OER electrocatalyst RuO2. The difference between this comparative example and Example 1 is that ZrCl4 and (NH4)2MoO4 are not added in step 1. The other steps and parameters are the same as those in Example 1 to obtain homemade RuO2.

[0044] Zr prepared in Example 1 0.05 Mo 0.05 Scanning electron microscope photos of RuO2 Figure 2 As shown, from Figure 2 It can be seen that Zr 0.05 Mo 0.05 RuO2 is irregularly spherical with protrusions and depressions on the surface.

[0045] The scanning electron microscope photo of RuO2 prepared in Comparative Example 1 is as follows Figure 3 As shown, from Figure 3 RuO2 can present a smooth and regular circular flake structure.

[0046] Zr prepared in Example 1 0.05 Mo 0.05 The transmission electron microscope photo of RuO2 is shown in Figure 4 As shown, from Figure 4 It can be seen that Zr 0.05 Mo 0.05 RuO2 is in the shape of particles, and the particle size is relatively uniform.

[0047] Zr prepared in Example 1 0.05 Mo 0.05 The selected area diffraction pattern of RuO2 is as follows Figure 5 As shown, from Figure 5 The (211), (110), and (101) crystal planes of rutile phase RuO2 can be seen.

[0048] Zr prepared in Example 1 0.05 Mo 0.05 RuO2, RuO2 prepared in Comparative Example 1 and standard XRD patterns are shown in Figure 6 As shown, from Figure 6 It can be seen that the XRD spectra of the two prepared samples are in good agreement with the rutile phase of RuO2. In this XRD spectrum, the strong signal intensities at 28.0°, 35.1° and 54.3° can be attributed to the (110), (101) and (211) crystal planes of RuO2, and the main crystal phase reflected is consistent with the TEM results. In addition, no characteristic peak signals of zirconium oxide and molybdenum oxide were detected, indicating that the doping of Zr and Mo elements did not destroy the rutile phase structure of RuO2.

[0049] Zr prepared in Example 1 0.05 Mo0.05 The XPS spectra of RuO2 and RuO2 prepared in Comparative Example 1 are as follows Figure 7 As shown, Figure 7 The a shows Zr 0.2 The full spectrum of RuO2 and RuO2 clearly shows Zr 0.2 The peaks of Zr 3d and Mo 3d orbitals appeared after RuO2, which further confirmed that Zr and Mo were successfully doped into RuO2. Since the XPS spectrum of Ru(3d) peak partially overlaps with the C(1s) peak, it is not suitable for oxidation state estimation. Therefore, the binding energy value of Ru 3p region is used to detect the oxidation state of ruthenium. Figure 7 In the Ru 3p 3 / 2 spectrum shown in (b), the peaks with binding energies of 458.0, 462.3, and 465.5 eV correspond to Ru 0 、Ru 4+ And Ru n+ (n>4). Compared with RuO2, Zr 0.05 Mo 0.05 The Ru 3p of RuO2 shifts to a higher energy level, and the electrons of Ru are transferred to a higher oxidation state. Figure 7 In the O1s spectrum shown in c, the peaks at 529.7, 531.5, and 533.0 eV can be attributed to lattice oxygen (OL), oxygen vacancies (O V ) and surface adsorbed oxygen (Oads). Figure 7 In the Zr 3d spectrum shown in d, the peaks of Zr 3d are concentrated around 181.4eV and 183.9eV, indicating that tetravalent Zr ions are the main form after doping. Figure 7 In the Mo 3d spectrum shown in f, the peaks of Mo3d are concentrated near 234.7 eV and 231.5 eV, indicating that pentavalent Mo ions are the main form after doping.

[0050] The double transition metal doped RuO2 acidic OER electrocatalyst Zr prepared in Example 1 was used respectively. 0.05 Mo 0.05 The electrode was prepared by using RuO2, the acidic OER electrocatalyst RuO2 prepared in Comparative Example 1, and the purchased commercial RuO2. The specific method was carried out according to the following steps:

[0051] 1. Pretreatment of carbon paper substrate The specific operation is as follows: take carbon paper with a thickness of 210 μm and an area of ​​1*1.5 cm, first soak it in 1M hydrochloric acid for 30 min to remove oxide impurities on its surface; then, ultrasonically soak the carbon paper in ultrapure water for 30 min to remove residual acid, and finally, ultrasonically soak it in anhydrous ethanol for 30 min to remove organic matter, and dry it in a vacuum oven at 60°C for 6 h to obtain a carbon paper substrate;

[0052] 2. Preparation of working electrode: Put the catalyst powder in a centrifuge tube, add 388 μL of anhydrous ethanol, 12 μL of 5 wt% Nafion solution, and 0.2 mg of PVDF, and then put it in an ultrasonic machine for 2 h to form a uniform suspension;

[0053] 3. Use a pipette to measure the suspension and evenly apply it on the carbon paper so that the catalyst loading is 1 mg cm -2 , and dried naturally to obtain electrodes; respectively denoted as Zr 0.05 Mo 0.05 RuO2 electrode, RuO2 electrode and commercial RuO2 electrode.

[0054] Zr 0.05 Mo 0.05 Application of RuO2 electrode, RuO2 electrode and commercial RuO2 electrode for electrocatalytic water splitting OER, the steps are as follows:

[0055] 1. Prepare the acidic solution 0.5M H2SO4: weigh 27.2mL of 98% concentrated sulfuric acid, dissolve it in 500mL of ultrapure water and stir evenly. After cooling, transfer it to a 1000mL volumetric flask and dilute it to 1000mL for later use;

[0056] 2. Prepare the working electrode: Use an electrode clamp to clamp the edge of the carbon paper of the electrode so that the area of ​​the electrode immersed in the 0.5M H2SO4 solution is 1*1cm;

[0057] 3. Electrocatalytic oxygen evolution reaction: All electrochemical tests were carried out in a three-electrode system at room temperature. During the reaction, platinum was used as the counter electrode, Hg / Hg2SO4 electrode as the reference electrode, and Zr 0.05 Mo 0.05 RuO2 electrode, RuO2 electrode or commercial RuO2 electrode were used as working electrodes, and 0.5 M H2SO4 was used as the electrolyte for all electrochemical tests; before the OER electrochemical test, the electrodes were activated by CV with 150 cycles and a scan rate of 300 mV·s -1 .

[0058] Figure 8 The Zr prepared in Example 1 is shown in a 0.05 Mo 0.05 OER polarization curves of RuO2 electrode, RuO2 electrode or commercial RuO2 electrode, Zr 0.05 Mo 0.05 RuO2 exhibits the best OER activity. Zr 0.05 Mo 0.05 RuO2 at 10 mA cm -2 , 20mA cm -2, 50mA cm -2 , 100mA cm -2 At current densities of 224 mV, 243 mV, 271 mV and 320 mV are required respectively. Figure 8 The Tafel curve fitting diagram is shown in Figure b. From this figure, it can be seen that Zr 0.05 Mo 0.05 The Tafel slope of the RuO2 catalyst is 91.2 mV dec -1 , lower than RuO2 (130.3mV dec -1 ) and commercial RuO2 (137.0mV dec -1 ), indicating that Zr 0.05 Mo 0.05 The OER process of RuO2 is faster.

[0059] Fig. 9 a is Zr prepared in Example 1 0.05 Mo 0.05 EIS impedance diagrams of RuO2, RuO2 prepared in Comparative Example 1 and commercial RuO2 catalysts. Fig. 9 It can be seen from a that Zr 0.05 Mo 0.05 RuO2 has the smallest semicircle diameter, the smallest charge transfer resistance (Rct), the fastest charge transfer rate, and faster reaction kinetics. Fig. 9 The b shows that Zr 0.05 Mo 0.05 Double layer capacitance C of RuO2, RuO2, and commercial RuO2 dl From the fitting diagram, we can see that Zr 0.05 Mo 0.05 RuO2 has the largest C dl value, reaching 121.9mF cm -2 , which is 1.8 times that of RuO2 and 2.2 times that of commercial RuO2. dl The value is linearly proportional to the electrochemically active surface area (ECSA), indicating that Zr 0.05 Mo 0.05 RuO2 has an electrochemically active area.

[0060] Fig.10 The Zr prepared in Example 1 is shown 0.05 Mo 0.05 RuO2 and commercial RuO2 at 10 mA cm -2 Stability test curve under current density. Fig.10 It can be seen that commercial RuO2 loses its activity rapidly within the first 10 h, while Zr 0.05 Mo 0.05RuO2 exhibited excellent stability within 200 h.

[0061] Fig.11 The Zr prepared in Example 1 is shown 0.05 Mo 0.05 RuO2 at 10 mA cm -2 XRD comparison diagram before and after stability test under current density. Fig.11 It can be seen that after 200h of stability testing, due to the existence of the Mo-O structure, oxygen vacancies are inevitably generated, causing the lattice to shrink and the characteristic peak to shift to a high angle.

[0062] Example 2: This example is to prepare double transition metal doped RuO2 acidic OER electrocatalyst Ti 0.05 Mo 0.05 RuO2, the difference between this embodiment and embodiment 1 is that "17.1 mg ZrCl4" in step 1 of embodiment 1 is replaced by "13.9 mg TiCl4", and the other steps and parameters are the same as those of embodiment 1.

[0063] Ti of this embodiment 0.05 Mo 0.05 RuO2 at 10 mA cm -2 , 20mA cm -2 , 50mA cm -2 , 100mA cm -2 The overpotentials are 249mV, 270mV, 329mV, and 367mV respectively.

[0064] Example 3: This example is to prepare double transition metal doped RuO2 acidic OER electrocatalyst Zr 0.05 Nb 0.05 RuO2. The difference between this embodiment and embodiment 1 is that "90.5 mg (NH4) 2 MoO4" in step 1 of embodiment 1 is replaced by "19.8 mg NbCl5". The other steps and parameters are the same as those of embodiment 1.

[0065] Zr in this embodiment 0.05 Nb 0.05 RuO2 at 10 mA cm -2 , 20mA cm -2 , 50mA cm -2 , 100mA cm -2 The overpotentials are 260mV, 287mV, 343mV, and 410mV respectively.

[0066] Example 4: This example is to prepare double transition metal doped RuO2 acidic OER electrocatalyst Zr 0.05 Tc 0.05RuO2. The difference between this embodiment and embodiment 1 is that "90.5 mg (NH4) 2 MoO4" in step 1 of embodiment 1 is replaced by "17.6 mg TcCl4". The other steps and parameters are the same as those of embodiment 1.

[0067] Zr in this embodiment 0.05 Tc 0.05 RuO2 at 10 mA cm -2 , 20mA cm -2 , 50mA cm -2 , 100mA cm -2 The overpotentials are 275mV, 312mV, 389mV, and 502mV respectively.

[0068] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A double transition metal doped RuO2 acidic OER electrocatalyst, characterized in that The chemical formula of the electrocatalyst is (M1) x (M2) y RuO2, wherein M1 is Zr or Ti; M2 is Mo, Nb or Tc; x=0.02~0.1, y=0.02~0.

1.

2. A method for preparing a double transition metal doped RuO2 acidic OER electrocatalyst according to claim 1, characterized in that: The method proceeds as follows:

1. Weigh RuCl3·xH2O, transition metal M1 salt, transition metal M2 salt and ethanol, dissolve in water, and stir magnetically for 0.5 to 3 hours to obtain a mixed solution; 2. Transfer the mixed solution to a polytetrafluoroethylene liner, cover it with a stainless steel outer liner, transfer it to a homogeneous reactor, heat it to 60-180°C and maintain it for 2-10 hours for high temperature reaction, cool it to room temperature after the reaction is completed, wash the product with pure water and ethanol alternately, collect it by centrifugation, and dry it in vacuum to obtain a precursor powder; 3. Place the precursor powder in a high-temperature furnace, heat it to 200-800°C and maintain it for 0.5-6 hours for annealing, and then cool it to room temperature to obtain a double transition metal-doped RuO2 acidic OER electrocatalyst.

3. The method for preparing a double transition metal doped RuO2 acidic OER electrocatalyst according to claim 2, characterized in that: The mass fraction of Ru in the RuCl3·xH2O described in step 1 is 37%.

4. The method for preparing a double transition metal doped RuO2 acidic OER electrocatalyst according to claim 2 or 3, characterized in that: The amount of the transition metal M1 salt described in step 1 satisfies the atomic ratio M1:Ru=(0.02-0.1):1; the amount of the transition metal M2 salt satisfies the atomic ratio M2:Ru=(0.02-0.1):

1.

5. The method for preparing a double transition metal doped RuO2 acidic OER electrocatalyst according to claim 2 or 3, characterized in that: The mass percentage concentration of RuCl3·xH2O in the mixed solution described in step 1 is 95% to 98%.

6. The method for preparing a double transition metal doped RuO2 acidic OER electrocatalyst according to claim 2 or 3, characterized in that: The volume percentage concentration of anhydrous ethanol in the mixed solution described in step 1 is 20% to 60%.

7. The use of a double transition metal doped RuO2 acidic OER electrocatalyst according to claim 1, characterized in that The application is to prepare the double transition metal doped RuO2 acidic OER electrocatalyst into an electrode for use in water electrolysis to produce hydrogen.

8. The use of a double transition metal doped RuO2 acidic OER electrocatalyst according to claim 7, characterized in that: The method for preparing an electrode using a double transition metal doped RuO2 acidic OER electrocatalyst is carried out in the following steps:

1. Pretreatment of the carbon paper substrate: first, the carbon paper is cut into a rectangle of 1*1.5 cm; then, hydrochloric acid, ultrapure water and anhydrous ethanol are used in an ultrasonic cleaning machine to remove the oxide on the surface of the carbon paper by ultrasonic cleaning, and then vacuum drying is performed to obtain a carbon paper substrate; 2. Add the double transition metal doped RuO2 acidic OER electrocatalyst to the dispersion, and then put it into an ultrasonic machine for ultrasonic treatment for 0.5 to 3 hours to form a uniform suspension; 3. Evenly drop the suspension onto the carbon paper substrate and allow it to dry naturally to obtain the electrode.

9. The use of a double transition metal doped RuO2 acidic OER electrocatalyst according to claim 8, characterized in that: The dispersion described in step 2 is prepared by mixing anhydrous ethanol, Nafion solution and PVDF; the mass fraction of the Nafion solution is 1 to 10 wt%; The volume ratio of anhydrous ethanol to Nafion solution is 970:30; each milliliter of the dispersion contains 0.1-0.9 mg PVDF.

10. The use of a double transition metal doped RuO2 acidic OER electrocatalyst according to claim 8 or 9, characterized in that: The loading amount of the double transition metal doped RuO2 acidic OER electrocatalyst on the carbon paper substrate described in step 3 is 0.5-2 mg cm -2 .

Citation Information

Cited By

  • Ruthenium molybdenum oxide nanorod electrocatalyst, preparation method and application

    CN120272973A

  • W-doped Co3O4 loaded Ru monatomic catalyst for acidic OER and preparation method of W-doped Co3O4 loaded Ru monatomic catalyst

    CN120575233A